2010
DOI: 10.1177/1420326x10383477
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Indoor concentrations of Radon and Thoron in homes in Bangalore, India

Abstract: Due to the legislation and general concern of radiation levels in dwellings in India, there is a need to continuously monitor the indoor concentrations of radon and Thoron in different geographical areas of Bangalore, which could be of great significance to exposure to occupants, particularly in living places. This paper presents the 222Rn and 220Rn concentrations measured in houses in 10 different locations in Bangalore. The data was continuously obtained for a period of 2 years since 2007, covering more than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…It is important to note that even though reduced ventilation rate would aid to enhance the radon concentration and that of its daughters in air, the enhanced radiation may be due to the presence of 226 Ra-rich soil or 226 Ra-containing components in building construction material. 21,22 The measurement of radon exhalation rate in soil is helpful to study radon health hazard. Some building materials may be responsible for increased indoor radon levels either due to their higher radon exhalation rates or due to their uranium/radium enrichment as compared to other materials depending on their micro-structure.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that even though reduced ventilation rate would aid to enhance the radon concentration and that of its daughters in air, the enhanced radiation may be due to the presence of 226 Ra-rich soil or 226 Ra-containing components in building construction material. 21,22 The measurement of radon exhalation rate in soil is helpful to study radon health hazard. Some building materials may be responsible for increased indoor radon levels either due to their higher radon exhalation rates or due to their uranium/radium enrichment as compared to other materials depending on their micro-structure.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted on the potential of physical built environments that could harm human health [26][27][28][29][30][31][32][33]. In these studies, more attention has been paid to the physical/physiological dimensions of health than to psychological and social dimensions.…”
Section: Theoretical Review On Holistic Health and Healthy Constructionmentioning
confidence: 99%
“…According to the currently available literature [20], the concentrations of Rn and Tn in the study area ranged from 17. The previous studies reported the activity concentrations of 226 Ra and 232 Th were found to vary from 8 to 110 Bq kg −1 with a mean of 26 Bq kg −1 , and from 17 to 100 Bq kg −1 with a mean of 53 Bq kg −1 , respectively.…”
Section: Introductionmentioning
confidence: 99%